An analysis on pronunciation of consonants’ sound positions in standard Turkish by primary school students [İlköğretim öğrencilerinin standart türkçedeki ünsüzleri sesletimleri üzerine bir inceleme] - Sönmez, H.; Hesapçioğlu, S. T. (Ankara University, 2017)
In this study the sounds, the smallest unit of oral communication, are analyzed. In the study, children’s ability of Turkish consonants is analyzed living in Muş city center at the ages of between 7 age and 6 months and 10 age and 6 months. The answers of the children are saved in the answer keys prepared for them and the analysis of collected data is actualized with the help of SPSS 15 program (Statistical Package for the Social Sciences). In the evaluation of the data descriptive statistics methods are benefited, answers given to questions are transferred to table as frequency and percentage. After analysis it is determined that age and gender is significant variables in pronunciation. It is observed that the ability of girls’ and boys’ pronouncing changes depending on the age. It is determined that all the ages of children participated in the study, pronounced the consonants differently or mispronounced depending on the position. It is concluded that in most of the age group, some sounds are pronounced accurately and successfully. © 2017, Ankara University. All rights reserved.
Keywords: Age; Gender; Pronunciation; Turkish consonants